Advances in acoustics and vibration : proceedings of the International Conference on Acoustics and Vibration (ICAV2016), March 21-23, Hammamet, Tunisia /: proceedings of the International Conference on Acoustics and Vibration (ICAV2016), March 21-23, Hammamet, Tunisia. ([2017]) - Unknown
No abstract available